Focal Ablation of Early-Stage Prostate Cancer: Candidate Selection, Treatment Guidance, and Assessment of Outcome. - Edison,E; Tariq,Shah T; Ahmed,HU (Urologic Clinics of North America, 2017)
Prostate cancer lesions smaller than 0.5 m3, or Gleason pattern 3, are likely clinically insignificant. Clinically significant disease is often limited to a single index lesion. Focal ablation targets this index lesion, maintains oncological control, and minimizes complications by preserving healthy prostate tissue. Template mapping biopsy or multiparametric MRI-targeted biopsies are used to identify appropriate index lesions. Multiple energy modalities have been tested, including high-intensity frequency ultrasound, cryoablation, laser ablation, photodynamic therapy, focal brachytherapy, radiofrequency ablation, irreversible electroporation. Outcome is assessed by biopsy of the target area, triggered by prostate-specific antigen measurements or MRI imaging, or performed per protocol at 12 months.